Determination of Mechanical Properties of the Concrete Affected by High Temperature by Destructive and Non-Destructive Test Methods - Demirel, Bahar; Yazıcıoğlu, Salih; Tuğla, Rukiye; Ay, Serhat (Fırat University, 2019)
In this study, the effects of the elevated temperature on concrete specimens prepared with different aggregate types were investigated. For this purpose, 4 different series were prepared by using CEM I 42,5 (N) type Portland Cement and four different types of aggregates (basaltic crushed aggregate, stream aggregate, limestone and pumice as lightweight aggregate). 100 mm and 150 mm cube concrete samples were prepared for each series.  When reached the specified curing age, prepared each concrete specimen was taken from the curing pool and exposed to high temperatures of 300 ºC, 600 ºC and 900 ºC respectively.  Control specimens of each series were stored at room temperature. The compressive strengths, ultrasonic pulse velocity and the adherence strength of the concrete samples exposed to these temperatures were examined. At the end of this study, the compressive strengths of the series exposed to high temperature are compared. It is observed that the series which is produced with basaltic crushed aggregate is least affected and the series which is produced with lightweight aggregate is the most affected from the elevated temperature. Pull-out tests were carried out to the all prepared series and it was found that the adherence strength between the concrete and the reinforcement decreased as the temperature increased.
Keywords: Engineering; Mühendislik